Business Incubation Performance in the Malaysian ICT Sector - Abdul Khalid, Fararishah Binti; Jabar, Juhaini; Ahmad Kayani, Aminuddin; Gilbert, David (Advances in Social Sciences Research Journal, 2017)
This paper presents research on ICT incubation performance in Malaysia detailing contrasting outcomes predicated upon a number of factors modelled in this study including ‘Selection Performance’, ‘Monitoring and Business Assistance Intensity’, ‘Resource Allocation’, and ‘Professional Management Services’. It also aims at addressing the lack of knowledge concerning the underlying components impacting on ICT incubation performance in Malaysia. Building on the theoretical work of researchers in the field such as Hackett & Dilts (2004; 2008) who analysed the literature in chronological order identifying five primary research orientations in incubation (incubator development; incubator configurations; incubatee development; incubator-incubation impacts; and theorising about business incubation); four research propositions were developed for this study. A total of 180 participants were asked to respond to a questionnaire and 118 useable responses were received yielding a response rate of 65.6%. The research results highlight that a ‘one-size-fits-all’ approach is inappropriate. Whilst the four propositions developed for this research were all confirmed, it is telling that highly performed incubator firms were very much in the minority. Interestingly, resources provided became less significant as incubatees became more profitable whilst targeted professional management services increased in significance suggesting that as profitability improves the need for capability development increases.